2014
DOI: 10.1016/j.ydbio.2014.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Role for endocytosis of a constitutively active GPCR (GPR185) in releasing vertebrate oocyte meiotic arrest

Abstract: Vertebrate oocytes are naturally arrested at prophase of meiosis I for sustained periods of time before resuming meiosis in a process called oocyte maturation that prepares the egg for fertilization. Members of the constitutively active GPR3/6/12 family of G-protein coupled receptors represent important mediators of meiotic arrest. In the frog oocyte the GPR3/12 homolog GPRx (renamed GPR185) has been shown to sustain meiotic arrest by increasing intracellular cAMP levels through GαSβγ. Here we show that GPRx i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…PKA inhibits the maturation signaling pathway through at least two points: mRNA translation and Cdc25C activation (Duckworth et al, 2002;Matten et al, 1994), consistent with the idea that it is acting as a safety mechanism to eliminate spontaneous maturation in the absence of a positive signal. Although challenging the accepted dogma, our model is supported by earlier studies (Gelerstein et al, 1988;Nader et al, 2014;Noh and Han, 1998;Schmitt and Nebreda, 2002) and the yinyang balance between the mPRβ and cAMP pathways effectively explains the discrepancies in the literature.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…PKA inhibits the maturation signaling pathway through at least two points: mRNA translation and Cdc25C activation (Duckworth et al, 2002;Matten et al, 1994), consistent with the idea that it is acting as a safety mechanism to eliminate spontaneous maturation in the absence of a positive signal. Although challenging the accepted dogma, our model is supported by earlier studies (Gelerstein et al, 1988;Nader et al, 2014;Noh and Han, 1998;Schmitt and Nebreda, 2002) and the yinyang balance between the mPRβ and cAMP pathways effectively explains the discrepancies in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…Surprisingly, knockdown of GPR185 is not sufficient to induce oocyte maturation (Deng et al, 2008;Ríos-Cardona et al, 2008), arguing that other GPCRs are involved in maintaining meiotic arrest. We have previously shown that (1) blocking exocytosis, while maintaining endocytosis, releases meiotic arrest, (2) P4 results in the internalization of GPR185 and (3) a GPR185 mutant that does not internalize is more effective at maintaining meiotic arrest (ElJouni et al, 2007;Nader et al, 2014). These data argue that P4 induces internalization of GPR185 and potentially other GPCRs that are involved in maintaining high levels of cAMP and PKA and thus meiotic arrest.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations